COVALENT CONJUGATION AND CHARACTERIZATION OF THE EBOLA NUCLEOPROTEIN 421-430 PEPTIDE WITH POLYACRYLIC ACID - Acar, Tayfun; Ucar, Burcu; Arayici, Pelin Pelit; Derman, Serap; Mustafaeva, Zeynep (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2020)
The main purpose of this study is the synthesis and characterization of the bioconjugates of polyacrylic acid and the Ebola virus synthetic peptide (421-430 sequence in virus nucleoprotein). The peptide-polymer bioconjugates were synthesized at various conjugation ratios with changing the peptide concentrations. The physicochemical characterization of the obtained bioconjugates was performed using Fluorescence Spectroscopy and Size Exclusion Chromatography. The optimum conjugation ratio was determined by considering the amount of unreacted peptide calculated by evaluating the two analysis methods. The obtained results showed that the conjugates were synthesized in average 50% reaction efficiency and the fluorescence intensity decreased in every conjugation ratio relative to the fluorescence intensity of the equivalent amount of peptide. The results indicate the conjugation reaction was performed successfully and the gamma (n(peptid)/n(PAA) ratio) = 9 conjugate was found the optimum conjugation ratio for this peptide and polymer. It is believed that the obtained results can be used as an antigenic peptide vaccine model against the Ebola virus in future studies.
Keywords: Ebola virus disease; Synthetic peptide; Polyacrylic acid; Conjugation; ANTIGENIC PEPTIDE; FLUORESCENCE; AFFINITY; ALBUMIN; Environmental Sciences & Ecology